Escolas públicas militarizadas: uma análise na perspectiva dos direitos humanos - Bueno, Bárbara Ferreira (2022)
This dissertation defended in the Graduate Program in Education of the Faculty of Education at UFG was developed in the line of State Research, Policies and History of . Its general objective is to investigate the tensions between human rights and the militarization of education in militarized public schools in Goiás. The specific objectives are: a) to analyze the historical elements, conceptions, tensions, advances and perspectives in human rights and human rights education; b) understand the militarization of education in conservative neoliberal times and the advances and setbacks of the right to education; c) analyze the tensions between human rights and the militarization of education in militarized public schools in Goiás, evaluating what was said and what was done. The question that motivated us to investigate was: what tensions involve human rights and the process of militarization of education in Goiás? The analysis is based on primary sources (documents) and secondary sources (books, articles and theses), thus, the method used will be bibliographic and documentary. It is expected to understand human rights and the right to education as a social right, from the Federal Constitution of 1988, the National Human Rights Program, among other documents. The study also has an analysis of the school regiment of the military college of the state of Goiás. The theoretical references will be: David Harvey (2008), Marilena Chauí (2000), Lilia Schwarcz (2014), Vera Maria Candau (2008), Erasto Fortes Mendonça (2015), Maria Victoria de Mesquita Benevides (2012), Marconi Pequeno, ( 2008), Luiz Carlos de Freitas (2012), Miriam Fábia Alves, Mirza Seabra and Neusa Sousa Rêgo (2018), Catarina de Almeida Santos (2021), among others. We will analyze how the historical, political and social context reflects on the education and human formation of militarized schools. This work intends to contribute to educational policies focused on human rights and the right to education. Through document analysis, we realized that the rules imposed on students violate human rights (dignity and equality), democratic management and ethnic-racial diversity. The principles and values of hierarchy, centrality, civics, patriotism and discipline are contrary to education for emancipation.